Expression and Clinical Significance of Cytoskeleton microtubule-associated - Tau in gastric carcinoma - Li, Chun-Hui; Hao, Meiling; Sahi, Rajina (Journal of College of Medical Sciences-Nepal, 2015)
Background and Objectives: Microtubules, the main components of spindles in the mitotic phase, can provide the suitable conditions for unlimited proliferation of tumor cells. Cytoskeleton microtubule-associated-Tau accelerates the progress of malignant tumor through microtubules. Currently, the expression of Cytoskeleton microtubule-associated-Tau in gastric cancer and the relationship between clinical pathological factors research has not yet been reported, so the report aims to elucidate the features of Cytoskeleton microtubule-associated-Tau expression in normal gastric tissue and gastric carcinoma tissue. Materials and Methods: The expressions of Cytoskeleton microtubule-associated protein-Tau protein and Cytoskeleton microtubule-associated protein-Tau mRNA were investigated in 60 cases of gastric carcinoma (cases) and 10 cases of normal gastric tissues (controls). Immunohistochemistry and RT-PCR were respectively used to detect the expression of Cytoskeleton microtubule-associated protein-Tau protein and Tau mRNA in the normal and carcinomatous gastric tissues. Results: The expressions of both cytoskeleton microtubule-associated protein-Tau protein and Tau mRNA in the carcinomatous gastric tissue were higher than in the normal gastric tissue (P<0.05). Likewise, both biomarkers were expressed significantly lower in the well-differentiated and moderately-differentiated gastric carcinoma was than in the poorly-differentiated one (P<0.05). Moreover, their expressions in the gastric carcinoma without lymph node metastasis was lower than in the gastric carcinoma with lymph node metastasis (P<0.05). Conclusion: The expressions of Cytoskeleton microtubule-associated-protein, Tau-protein and Cytoskeleton microtubule-associated-protein, Tau-mRNA were significantly different between the normal gastric tissue and the gastric carcinoma tissue, and were correlated with the degree differentiation and lymph node status. JCMS Nepal. 2015;11(3):6-11.